Internalisation of externalities: who bears the cost of pollution control? - Rahim, Khalid Abdul (Kluwer Academic Publishers, 1991)
The impact of environmental regulations on the welfare of Malaysian palm oil growers, producers, and refiners are evaluated in an open-economy model. The estimated incremental effects of effluent standards and changes have been specifically rather small, with the exception of those upon the growers, but the cumulative effects have been considerable.